Jenis Ikan Dominan, Kontinyuitas Penjualan dan Penetapan Harga Ikan pada Pasar Pengecer di Kodya Ambon dan Maluku Tengah - Bernard B. de Rosari; Abdul Choliq (Jurnal Agro Ekonomi, 1997)
IndonesianA research has been done to see the dominant fish sold, the continuity of fish supply, and the influence of the quantity of certain fish sold and prices of the other fish to the fish selling price determinant at retailing markets in Ambon and Central Maluku. Three markets were chosen, they were Pasar Rumah Tiga, Pasar Lama Ambon and Pasar Binaya Masohi, Central Maluku. Survey method was used in the research. Time series data were collected every three weeks from September 1995 to March 1996. The results showed, that the dominant type of fish sold continously in Pasar Rumah Tiga were Scads, Frigate tuna,"Skipjack and Trevalies; in Pasar Lama ambon were Mackerel, Frigate tuna, Skipjack and Scads; in Pasar Binaya Masohi were Mackerel, Frigate tuna, Trevalies and Scads. The fish whose selling price was not influenced by the volume supplied and by other fish prices were Skipjack and dried anchovies in Pasar Rumah Tiga, and Frigate tuna, Garfish, Smoke-grilled Skipjack and Tuna in Pasar Binaya (p 10% ). Increase in supply volume caused the decrease in sellingprice, of Mackerel (Rp 19/kg; p %) and frozen Pomfret ( Rp 32/kg; p 1%) in Pasar Lama Ambon and fresh Coral fish ( Rp 92/kg; p 5%) in Pasar Binaya. The prices of several type of fish were pairly substitute and complement each other.